GEODYNAMIC ACTIVITY OF MODERN STRUCTURES AND TECTONIC STRESS FIELDS IN NORTHEAST ASIA - L. P. Imaeva; G. S. Gusev; V. S. Imaev; S. V. Ashurkov; V. I. Melnikova; A. I. Seredkina; Л. П. Имаева; Г. С. Гусев; В. С. Имаев; С. В. Ашурков; В. И. Мельникова; А. И. Середкина (Geodynamics & Tectonophysics, 2017)
Based on the analysis of changes in the stress-strain state of the crust at the boundary of the Eurasian and North American tectonic plates, we develop a dynamic model of the main seismogenerating structures inNortheast Asia. We have established a regularity in changes of geodynamic regimes within the interplate boundary between the Kolyma-Chukotka crustal plate and the Eurasian, North American and Pacific tectonic plates: spreading in the Gakkel Ridge area; rifting in the Laptev Sea shelf; a mixture of tectonic stress types in the Kharaulakh segment; transpression in the Chersky seismotectonic zone, in the segment from the Komandor to the Aleutian Islands, and in the Koryak segment; and crustal stretching in the Chukotka segment. Анализ изменений напряженно-деформированного состояния земной коры, проведенный вдоль границы Евразийской и Североамериканской литосферных плит, позволил обосновать динамическую модель главных сейсмогенерирующих структур территории северо-востока Азии. В пределах единой межплитной границы, отделяющей Колымо-Чукотскую коровую плиту от Евразийской, Североамериканской и Тихоокеанской литосферных плит, наблюдается закономерная смена геодинамических режимов: спрединг хребта Гаккеля; рифтогенез на шельфе моря Лаптевых; смешанное поле тектонических напряжений в Хараулахском сегменте; транспрессия в сейсмотектонической зоне Черского, на участке от Командорских до Алеутских островов и в Корякском сегменте; растяжение в Чукотском сегменте.